Restorative Justice Against Child Abuse - Sutanto, Sutanto (Universitas Dharmawangsa, 2024)
The crime of child molestation is interesting to study, especially regarding legal arrangements and countermeasures, when associated with efforts to apply the concept or restorative justice system (restorative justice system), which is a system developed in the concept of criminal law to resolve certain cases in the corridors of the criminal justice system (criminal justice system), both at the level of Investigation, investigation, prosecution and examination of court hearings.Based on this, the authors are interested in conducting research, namely to find out how the practice of examining cases of sexual abuse of minors in an effort to apply Restorative justice and also find out what factors hinder the practice of resolving cases of sexual abuse of minors through Restorative Justice. In this study, the type of research used is normative juridical research and empirical juridical research. Normative juridical research is research that comes from library data or secondary data, (primary legal materials and secondary legal materials), especially the provisions of legislation that have synchronization with the title and formulation of the problem. This study is expected as input in the framework of the development of criminal justice system policy (criminal justice system) in relation to aspects of legal protection against the crime of sexual abuse of minors as well as the process of resolving cases of sexual abuse.